2018
DOI: 10.2147/ahmt.s147896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of ledipasvir/sofosbuvir in the treatment of adolescents and children with hepatitis C

Abstract: Chronic infection with hepatitis C virus (HCV) affects an estimated 0.1%–2% of the pediatric population in the United States. While the clinical course in young children is indolent, adolescents who contract HCV have a disease course similar to adults, with a 26-fold increased risk of chronic liver disease-associated mortality, hepatocellular carcinoma, and need for curative liver transplantation. Furthermore, adolescent patients are entering childbearing age and carry a risk of passing HCV to their offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Since an effective treatment is now available, it is important to diagnose and treat all children who are chronically infected by HCV. First, for adolescent patients and children, the SOF/LDV combination allows to achieve SVR rates of 98% [7,22]. Moreover, an ongoing Phase II, multicenter open-label trial (NCT 02249182) reported no serious adverse events in HCV1-infected patients during treatment [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since an effective treatment is now available, it is important to diagnose and treat all children who are chronically infected by HCV. First, for adolescent patients and children, the SOF/LDV combination allows to achieve SVR rates of 98% [7,22]. Moreover, an ongoing Phase II, multicenter open-label trial (NCT 02249182) reported no serious adverse events in HCV1-infected patients during treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…More studies are necessary to explore whether the presence of these variants correlates with treatment failure in children. To the best of our knowledge, the ongoing clinical trials including adolescent aged 12–17 years are evaluating efficacy and safety of treatment, including adverse events [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation